Mesurer l’horizon de son pas. La marche dans l’écriture (XVIIIe-XXIe) - Françoise Rigat (Seminario di filologia francese, 2021)
Our article talks about what is known in sociological terms as itinérance: the Walk. A Walk in nature has, just like walking, its own literary and linguistic expressions. Many writers, from Jean-Jacques Rousseau to our modern day, when addressing the concept of Wilderness, have addressed what "Walking on foot" signifies. This document aims to give body to the word "Walk": to understand its new clothes (sport Walking, extreme Walking, cultural Walking) and to investigate what the word really means as well as how it has been used historically, socially and culturally.